2014
DOI: 10.21608/jpp.2014.64719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mineral, Organic and Biofertilization on Growth , Yield and Quality of Cantaloupe

Abstract: Two field experiments were carried out in a private farm at Gamassa district, Belqas Center, Dakahlia Governorate, Egypt, during the two successive summer growing seasons of 2013 and 2014 to study the effect of mineral nitrogen fertilizer rates, organic manure and foliar fertilization treatments with biofertilizers , biostimulants as well as their interactions on growth and yield of cantaloupe cv. Primal. The field experiments were laid-out in strip-split plot design with three replications. The most important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other results show that Bio-N inoculation, in the presence of 50% the recommended mineral fertilizer, could parallel the yield of fully fertilized corn [8]. Several researchers reported that inoculation of some plants with bio fertilizers (singly or in different combinations with mineral fertilizers) improved plant growth, yield and chemical composition [9][10][11][12]. Moreover, several researchers justified the idea that nutrients like N may be taken up through roots and leaves and may spread within the plant [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Other results show that Bio-N inoculation, in the presence of 50% the recommended mineral fertilizer, could parallel the yield of fully fertilized corn [8]. Several researchers reported that inoculation of some plants with bio fertilizers (singly or in different combinations with mineral fertilizers) improved plant growth, yield and chemical composition [9][10][11][12]. Moreover, several researchers justified the idea that nutrients like N may be taken up through roots and leaves and may spread within the plant [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%